Equally weighted multivariate optimization of feeding rate for sub‐yearling great sturgeon (Huso huso) using desirability function model. Issue 3 (7th October 2021) - Mani, Amir; Ebrahimi, Eisa
Abstract: Due to a lack of accurate information for appropriate sturgeon nutrition management, this study was conducted to determine the optimum feeding rate for sub‐yearling great sturgeons ( Huso huso ) with an average initial weight of 94.01 ± 4.36 g using the desirability function model. The feeding trial lasted for 60 days after acclimatization. This experiment was conducted in a completely randomized design with six different feeding rates (0.5, 1, 1.5, 2, 2.5, and 3% of body weight day −1 ) and three replicates for each feeding level. Daily diet of each experimental tank was divided into three different meals. The average water flow rate for each experimental tank was 1.5 L min −1 and the water temperature was adjusted to 22.7 ± 1.1.4 °C. To the best of our knowledge, this is the first report on multivariate optimization of feeding rate based on both specific growth rate and feed conversion ratio by the desirability function model. Obtained results indicate that optimum specific growth rate, feed conversion ratio, and economic efficiency for sub‐yearling great sturgeons with a weight range of 94.01 ± 4.36 g up to 350.25 ± 13.18 g occurred at a feeding rate of 1.89% body weight day −1 .